The dynamic molecular landscape of malignant melanomas arising from congenital or common nevi. Issue 3 (2019) - Harou, Olivier; Tondeur, Garance; Descotes, Françoise; Balme, Brigitte; Depaepe, Lauriane; Bringuier, Pierre-Paul; Caramel, Julie; Thomas, Luc; Dalle, Stéphane; Lopez, Jonathan
No abstract available